Kualitas Pelayanan Pasien Peserta BPJS di RSUD Lembang Kabupaten Bandung Barat (KBB) - Agusti, Zahra Rizqita; Kurhayadi, Kurhayadi; Mulayti, Yuyun (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
One of the public services that is highly considered by the wider community is health services because health services in Indonesia are still not of good quality. The health service problems that are occurring in Indonesia today are caused by the uneven distribution of quality health services for all Indonesian people in the process of providing services, for example regarding service discrimination with the service itself. Health services were not optimal, therefore the Indonesian government made a health program to deal with service problems, namely the BPJS (Health Insurance Organizing Agency) program. This study aims to determine the quality of service for BPJS participant patients in Lembang Hospital. The method used in this study is a qualitative method in a way that describes synergistic problems when the research is carried out. Data collection techniques are carried out by observation, interviews and documents. The instruments used in this study were observation sheets, interview sheets, and structured documentation made by the researchers themselves. The results of this study show that service to patients participating in BPJS at the Lembang Hospital is in the requirements are clear, but there are still some obstacles in terms of the quantity, quality of human resources and infrastructure in the Lembang Hospital and the attitude of employees when serving patients.